エンテロウイルス７１に対するヒト化抗体 (2019)
本発明は、手足口病（ＨＦＭＤ）の病原体であるエンテロウイルス７１（ＥＶ７１）に対するヒト化抗体、並びにこれらの抗体を含む医薬組成物、並びにＨＦＭＤの治療、予防法及び診断におけるそれらの使用方法を提供する。これらの抗体は、ＨＦＭＤを有するヒト被験体、又は例えば感染個体への曝露の結果としてＨＦＭＤのリスクがあるヒト被験体への使用に好適である。【選択図】図１ The present invention provides humanized antibodies against Enterovirus 71 (EV71), a causative agent of hand, foot, and mouth disease (HFMD), as well as pharmaceutical compositions comprising these antibodies and methods of their use in the treatment, prophylaxis, and diagnosis of HFMD. These antibodies are suitable for use in human subjects with HFMD or those at risk of HFMD, for example as a result of exposure to infected individuals.